The prosopographic portrait of the ukrainian editor in forewords and dedications to church books of the 17—18th centuries - Курганова, Олена (Український історичний журнал, 2023)
The aim of this article is to show the heuristic potential of comparative analysis of forewords, dedications, and afterwords in Ukrainian old-printed church editions for portraying the image of the baroque editor. The research methodology is based on a prosopographic analysis of the personality of the Ukrainian editor, as refl ected in the forewords, dedications, and afterwords of old-printed church books. The scientific novelty of the research lies in the innovative utilization of forewords, dedications, and afterwords to Ukrainian old-printed church editions as historical micro-sources of editor’s personality exploration. This kind of source is regarded as a manifestation of a value system and pragmatic intentions that are common for the social group, connected with the work of Ukrainian printing houses of the early modern period. Conclusions. The prosopographic portrait of the Ukrainian church book of the seventeenth-and eighteenth-century editor reveals in a complex of mutually exclusive characteristics. On the one hand, the baroque editor portrays himself as a spiritual leader who cares for the church community by performing tangible acts such as providing books, which are critical for the salvation of souls in the battle against sin. This edge of the editor’s personality acknowled ges God’s help in all stages of book publishing and manifests a true belief in God’s providence to take care of the book aft er its release. On the other hand, the editor of the church book reveals himself as a profit-seeker. This edge of the editor’s personality is demonstrated by his readiness to use a powerful person’s protection or, if relevant, his own social privileges to get fi nancial advantages for the printing house. The image of a generous patron who supports the development of book printing is depicted in texts of dedications to church editions as an attempt to build up the fashion for fi nancial support of church book printing, presenting it as a virtue worthy of a heavenly reward. The competitiveness of church book editors is evidenced by the discussions on the accuracy of translation and reliability of sources, which are seen in the forewords to particular editions of books for church ceremonies. Such a dualistic form of the editor’s self-presentation reflects the typical worldview of the Ukrainian baroque connection of selfless service to God, with expectations not only for salvation in eternity but also for prosperity in the earthly life.